Pusong mamon: Nel Nodding's care ethics in the Filipino educational setting - Dela Cruz, Noelle Leslie G. (Animo Repository, 2013)
This paper evaluates Nel Noddings’s view of moral education in the context of teaching in a Philippine university. It first presents the key aspects of Noddings’s ethical theory, identifying her three strategic moves as follows: the dissolution of the public/private split, the replacement of justice-based punishment system with a caring system, and the promotion of care work as the core of education itself. Through a discussion of two cases of academic dishonesty, the author assesses the merits of these strategies and recommends a re-conceptualization both of care ethics and the existing educational paradigm.